Nursing performance in the control of nosocomial infection by multiresistant bacteria: a bibliographic review - Rêgo, Thalita Cleisla Rodrigues (2023)
Objective: In this bibliographic research, the aim was to analyze the role of the nursing professional in the control and prevention of hospital infection by multiresistant bacteria, with the hypothesis that many cases can be avoided.Method: Fifteen articles found in the Scientific Electronic Library Online (Scielo), PubMed, RevistaBrasileiraemPromoção da Saúde, MedLine and Literatura Latino-Americana e do Caribe emCiências da Saúde (LILACS) databases were analyzed and interpreted qualitatively, taking into consideration inclusion and exclusion factors such as the publication period and approach to the theme.Results: From the systematization of the articles, it was found that the orientation of patients, companions and visitors regarding measures to prevent cross-infection, as well as the cautious use of hygiene techniques and PPE by nursing professionals to prevent the spread of these bacteria constitute, essentially, the role of nurses in the fight against this type of infection.Conclusion: Continued education of the team through group discussions and reflections is believed to be the best way to change the employees' behavior, leading to a reduction in the high rates of hospital infection caused by resistant bacteria.